Informativeness of key audit matters: Evidence from China - GOH, Beng Wee (Institutional Knowledge at Singapore Management University, 2024)
This study examines whether the key audit matters (KAMs) disclosed in expanded audit reports as a part of recent regulatory reforms are informative for investors in an emerging economy setting. Using the recent adoption of expanded audit reports for firms listed exclusively in Mainland China, we find robust evidence that the abnormal trading volume and earnings response coefficients (ERCs) are higher and that stock price synchronicity is lower during the postadoption than preadoption period. In additional tests, we find evidence that KAMs are more informative for non-state-owned enterprises (non-SOEs), smaller firms, and firms with a smaller analyst following. Finally, we find that investors respond to the characteristics of KAM disclosures, providing corroborative evidence of the informativeness of these disclosures. Overall, our study provides systematic evidence that KAMs are incrementally informative for investors in an emerging economy.